Nilai dan prinsip antikorupsi dalam pancasila sebagai sistem etika - Aini, Nahdiyah Intan Qurrotu (Maliki Interdisciplinary Journal, 2026)
The role of Pancasila as an ethical system related to the instilling and strengthening of anti-corruption values. Corruption is considered a violation of basic ethics that contradicts the principles of Pancasila, from Belief in One Almighty God to Social Justice. Using a qualitative descriptive approach, this paper examines the five main values ​​of Pancasila: religiosity, humanity, unity, democracy, and justice, along with the identification of anti-corruption principles that can be taken from each principle, such as honesty, caring, independence, discipline, responsibility, hard work, simplicity, courage, and justice. The results of the study indicate that the application and appreciation of Pancasila as a comprehensive ethical system is a solid moral foundation for building an anti-corruption culture in Indonesia in the modern era. This study also provides practical suggestions for educational institutions and law enforcement agencies to use Pancasila as a philosophical and ethical basis in efforts to uncover and prevent corruption.